2017
DOI: 10.1051/e3sconf/20172401007
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the impact of an overlying coal seam edge using seismic profiling of refracted Pwave velocity

Abstract: This paper presents the results of seismic profiling along the sidewalls of two headings of a longwall in a coal-seam at a depth of about 850 and 870 metres in a coal mine in the Upper Silesian Coal Basin, Poland. The seismic profiles were located in a zone of impact of the same overlying edge of the coal-seam located about 40 m above. This study was interesting from that point of view since there were no other geological and mining factors present which could disturb the impact of the coal seam edge. The prof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…1) or measured velocity in the region outside of anomaly. The error of the measured velocity did not exceed 50m/s [18].…”
Section: Methods Of Processing and Interpretationmentioning
confidence: 76%
See 1 more Smart Citation
“…1) or measured velocity in the region outside of anomaly. The error of the measured velocity did not exceed 50m/s [18].…”
Section: Methods Of Processing and Interpretationmentioning
confidence: 76%
“…One of the basic ones is stress concentration in coal seams which occurs in particular as a result of the impact of the edges and remnants of adjacent coal seams [7][8][9]. The magnitude of such impacts is commonly recognized by seismic profiling [1,[10][11][12][13][14][15][16][17][18]. Refracted P-wave velocity profiling used to be performed according to the Dubiński method [10] updated in the work of Dubiński and Konopko [1].…”
Section: Introductionmentioning
confidence: 99%
“…An additional problem is related to the fact that the velocity of the determined Pwave does not differ significantly from the velocity of the refracted S-wave in shale layers in the roof and the bottom of the coal seam (Fig. 2) [14]. At greater distances from the excitation point, the first breaks of the refracted P-wave in shale layers overtakes or distorts the first breaks of the P-wave in the coal seam.…”
Section: Figmentioning
confidence: 99%
“…Szreder and Barnas [14] reported that "seismic profiling in underground excavations was also carried out for different purposes in other geological conditions for example: in a salt body to estimate the width of the fracture zone in the side-walls of excavations [15] and also in tunneling [16][17]"…”
Section: Introductionmentioning
confidence: 99%